2017
DOI: 10.1111/opo.12361
|View full text |Cite
|
Sign up to set email alerts
|

Optical characteristics of Alvarez variable‐power spectacles

Abstract: Within their designed power ranges, optical performance of currently-available Alvarez variable-power spectacles appears to be adequate to correct the distance and near vision of spherical ametropes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Monocular spherocyclindrical refractive errors were measured using a novel self‐refraction method (SfR) that used adjustable glasses (AdLens, AdLens Ltd) mounted in a ring holder (Figure ). In contrast to the original formulation by Alvarez, it was recently shown that these lenses have a moderate amount of astigmatism in the central optical area and it is therefore possible to separate different meridians of interest.…”
Section: Methodsmentioning
confidence: 92%
“…Monocular spherocyclindrical refractive errors were measured using a novel self‐refraction method (SfR) that used adjustable glasses (AdLens, AdLens Ltd) mounted in a ring holder (Figure ). In contrast to the original formulation by Alvarez, it was recently shown that these lenses have a moderate amount of astigmatism in the central optical area and it is therefore possible to separate different meridians of interest.…”
Section: Methodsmentioning
confidence: 92%
“…In an interesting paper, Barbero & Portilla explore the way in which power and magnification are linked in progressive addition lenses (PALs) and consider their results in relation to the problems of distortion and blur experienced by some wearers of such lenses. Radhakrishnan & Charman present measurements of the optical performance of examples of some current commercial variable‐power spectacles and conclude that these might be useful to at least some presbyopes.…”
Section: Methods Of Correctionmentioning
confidence: 99%
“…24 The oblique astigmatism of the eye also has a major impact upon the blur patterns on the peripheral retina when the visual axis is directed through the lens centre. The typical oblique astigmatism of the eye rises from about 1 D at a field angle of 20 degrees to around 2.5 D at 40 degrees, 25 thereby introducing corresponding additional spherical and cylindrical blur. Nevertheless, Figure 2b would be expected to give a reasonable prediction of the general features of the images.…”
Section: Key Pointsmentioning
confidence: 99%